PENGARUH INFLASI DAN NILAI TUKAR TERHADAP RETURN SAHAM YANG DIMEDIASIKAN OLEH KINERJA PERUSAHAAN - Otniel Hongdoyo; Fransiskus Randa; Suwandi Ng (AJAR, 2021)
The purpose of this study was to investigate the effect of inflation and exchange rate to company performance, investigate the effect of company performance to stock returns and investigate the effects of inflation and exchange rate that is mediated by the performance of the company. The population used was the company in LQ 45 listed on the Indonesia Stock Exchange by year study period from 2017 to 2019. The total sample is 21 companies for each year selected by purposive sampling method and using secondary data, the annual report. The analytical method used is the method of path analysis and hypothesis testing mediation conducted by using Sobel test. The analysis showed that inflation and the exchange rate had a negative effect and no significant effect on the performance of the company. The company's performance has a positve effect and no significant effect on stock returns. This study also show that the company's performance did not play a role in mediating the relationship of inflation and exchange rate.